Comparison of external load indicators between official matches and sport-specific training in semi-professional soccer players: focus on intensity and strength - Pillitteri, G.; Giustino, V.; Messina, G.; Petrucci, M.; Rossi, A.; Bellafiore, M.; Iovane, A.; Thomas, E.; Bianco, A.; Palma, A.; Battaglia, G. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: The aim of this study was to investigate any differences in external load indicators (ELi) between official matches (OM) and sport-specific tasks in semi-professional soccer players. METHODS: Among 28 semi-professional soccer players, 1932 observations (age: 25±6 years, height: 183±6 cm, weight: 75.2±7 kg; FC Palermo, Palermo, Italy) were collected through GPS devices (Qstarz BT-Q1000EX, 10 Hz; Qstarz International Co., Ltd., Taipei, Taiwan) and the related software (LaGalaColli V: 8.6.4.3; Spinitalia Srl, Rome, Italy) during the season 2019-2020. Participants were monitored during OM, friendly matches (FM), small sided games (SSG), and match-based exercises (MBE), considering the percentage of intense accelerations (%int. acc.), percentage of intense decelerations (%int. dec.), and passive recovery time /min (PrT/m) as Eli. RESULTS: We detected the highest mean value for PrT/m in OM and the lowest in MBE and SSG (18.36±4.38 and 13.4±5.26 and 13.4±4.29 (s/min), respectively). The lowest mean values of %int. acc. and %int. dec. were found in OM and the highest in SSG (8.64±1.52 vs. 13.02±3.14 and 9.25±1.56 vs. 15.68±3.14, for %int. acc. and %int. dec., respectively). Significant differences between the four tasks for all the ELi considered (P<0.001). The post-hoc pairwise comparisons revealed significant differences for all the ELi between all tasks (P<0.001) except for the %int. acc. between MBE vs. FM (P=0.003). No significant difference was found in PrT/m between MBE vs. FM and SSG vs. FM. CONCLUSIONS: ELi are in accordance with the performance model by achieving better values in training than OM, suggesting the fundamental role of GPS for monitoring external load in soccer.